Misuse of The Notary's Right to Reject in Investigation of Criminal Cases Regarding Deeds He Made - Iswahyudi, Iswahyudi; Arifulloh, Achmad (TABELLIUS: Journal of Law, 2025)
Abstract. Notaries have an important role in ensuring legal certainty through the creation of authentic deeds. However, in practice, the right of denial held by notaries often becomes an obstacle in the investigation of criminal cases involving deeds they have made. This right aims to protect the confidentiality of the position and the interests of the client, but on the other hand, it can hinder the law enforcement process when the notary refuses to comply with the investigator's summons. This study uses a normative legal approach, meaning that the study was conducted using a literature study approach and a statute approach. Data type the type of data uses secondary data obtained from a literature study. The analysis in this study is prescriptive. The results of this study indicate that although notaries are given legal protection to maintain their professional independence, there is tension between the notary's legal obligation to comply with investigators' summons and the right to maintain the confidentiality of documents created. Failure to comply with investigators' summons can result in administrative or criminal sanctions, as well as hinder investigations and law enforcement. To maintain a balance between the protection of the notary profession and law enforcement, there needs to be strengthening of professional supervision and revision of regulations related to investigation procedures for notary documents. This study also highlights the importance of ongoing education for notaries regarding their rights and obligations, as well as training for investigators to understand the limitations of their authority in handling notary documents, in order to avoid abuse of authority and maintain the principle of due process of law.Keywords: Authentic Deed; Criminal Investigation; Notary; Right of Refusal